Injuries in taekwando: systematic review - Thomas, R. E.; Thomas, B. C.; Vaska, M. M. (The Physician and Sportsmedicine, 2017)
Objectives: Assess rates/1000athletic encounters(AE) in Taekwondo of injuries/age/gender/type/location.